Analisis Komunitas Online Tenoon.id: Dinamika dan Pemberdayaan Terhadap Kaum Disabilitas dan Perempuan di Indonesia - Oktaviana, Jesica; Setiadi, Devina Karsten; Furnando, Riko (Jurnal Dinamika Sosial Budaya, 2022)
Abstract: Human and communication are inseparable, because basically humans have to communicate and also have shared motivations that become a community. Due to the rapid development of the times and technology, community systems and ecosystems have transformed into virtual communities such as virtual Tenoon.id communities. But how they can maintain and improve these crucial social relationships to support the Tenoon.id in the future. In general, there are social relationship-breaking conflicts between internal members of the community that trigger the division of a community. Therefore, this study discusses how Tenoon.id maintains the kontan and unity in existing social relations to carry out a work plan that is a mandatory activity and daily dynamics of Tenoon.id. The results of this study are in Tenoon.id social relationships that are well established and effective, especially when Tenoon.id utilize existing technology to be able to adapt to the situation during the Covid-19 pandemic, and all of these things also do not close the possibility of small problems such as errors in receiving information, late meetings, and so forth.
Keywords: Online Community; Tenoon.id; social relation